Novel 3-dimensional classification of cervical abrasion using CBCT: A comprehensive analysis - Tarun Kumar Singh; Ashish J. Johnson; Aakash Gupta; Ikroop Gill (Elsevier, 2024)
Introduction: Tooth cervical abrasion (CA) is a prevalent non-carious cervical lesion that poses challenges for accurate diagnosis from periapical radiographs due to difficulties in assessing the lesion's extent, associated bone loss, and pulpal involvement. The presence of overlying bone structures on the palatal side when lesions are located on the buccal side, or vice versa, further complicates radiographic interpretation. So it is important to define the lesions in all three dimensions. Objective: To provide a three-dimensional descriptive classification for cervical abrasion lesions using Cone Beam Computed Tomography (CBCT). Method: A total of 50 patients with cervical abrasion were selected for the study. From these patients, teeth (n = 10) from each of the four different quadrants were chosen. A CBCT scan with a 6 × 6 cm field of view (FOV) was performed, and the DICOM files of the cervical lesions were transferred to 3-D imaging software. The CBCT images of the cervical abrasion lesions were assessed at the level of the deepest point of the lesion along the long axis of the tooth in both axial and sagittal planes. The height (A), buccolingual dimension (B), circumferential spread (C), and remaining dentine thickness (D) were evaluated and classified using new scoring criteria for each dimension. The reliability and reproducibility of the classification were assessed to ensure its clinical applicability. Conclusion: CBCT can be utilized to classify tooth cervical abrasion in endodontics, enhancing diagnosis, analysis, and treatment outcomes. This three-dimensional view facilitates easier communication among clinicians, allows for tailored treatment approaches, and opens new avenues for research.